Phylogenetic relationships between the tuco-tucos (Ctenomys, Rodentia) of the corrientes group and the C. pearsoni complex - Caraballo, Diego Alfredo (2016)
Lineages delimitation is of extreme importance in evolutionary biology and constitutes an essential tool in basic and applied fields including conservation. This study faces the delimitation problem of two closely related species complexes of South American rodents of the genus Ctenomys (tuco-tucos). The corrientes group and the C. pearsoni complex showed unclear and conflicting relationships in previous phylogenies. In this study we performed a molecular phylogenetic analysis by enlarging the number of representatives of each group and including sequences of three mitochondrial loci (the complete cytochrome b coding sequence, and partial regions of the cytochrome oxydase I gene and the D-loop of the control region). This expansion resulted in the largest data matrix used to study these groups up to now. The trees obtained using Bayesian Inference and Maximum Parsimony methods show the corrientes group and the C. pearsoni complex as monophyletic sister clades. These results together with higher values of intergroup compared to intragroup genetic distances, indicate that the corrientes group and the C. pearsoni complex are differentiated lineages. The resulting tree topology is in agreement with a scenario of independent chromosomal rearrangements fromthe ancestral karyomorph 2n=70 NF=84 leading to the ample chromosomal diversity that characterizes both groups.